FORMULASI DAN UJI AKTIVITAS ANTIBAKTERI FRAKSI DAUN JELATANG (URTICA DIOICA L.) TERHADAP STAPHYLOCOCCUS EPIDERMIDIS - Akbar, Muh. Rezki Ramadhan Ali; Karim, Suhrah Febrina; Majid, Bahri (Fakultas Farmasi Universitas Buana Perjuangan Karawang, 2024)
Closed feet and long-term activities cause sweaty feet and damp conditions around the feet can cause odor. Foot odor is caused by a buildup of bacteria that breeds on damp feet. Some bacteria that cause foot odor include Staphylococcus epidermidis. Nettle leaf fractions (Urtica dioica L.) contain flavonoids, tannins, saponins and alkaloids which work as antibacterials for smelly feet. This research aims to determine whether the nettle leaf fraction (Urtica Dioica L.) can be formulated into a footspray preparation and what the activity of the nettle leaf fraction (Urtica Dioica L.) footspray preparation is on the growth of Staphylococcus Epidermidis bacteria. This research is an experimental research using methods of maceration, fractionation, formulation, evaluation of footspray preparations and testing of bacterial activity at concentrations of 12%, 13% and 14% using the disc diffusion method. The results of this research for formula concentrations of 12%, 13% and 14% meet the requirements for evaluating footspray preparations. Bacterial activity testing at concentrations of 12%, 13% and 14% had an average zone of inhibition of 15.1 mm (strong), 15.5 mm (strong), 16 mm (strong), respectively. It was concluded that the nettle leaf fraction (Urtica dioica L.) could be formulated as a footspray preparation and had antibacterial activity with the average zone of inhibition for each concentration being relatively strong in inhibiting the growth of Staphylococcus Epidermidis bacteria.